0.6x+2=0.7+2

Simple and best practice solution for 0.6x+2=0.7+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.6x+2=0.7+2 equation:


Simplifying
0.6x + 2 = 0.7 + 2

Reorder the terms:
2 + 0.6x = 0.7 + 2

Combine like terms: 0.7 + 2 = 2.7
2 + 0.6x = 2.7

Solving
2 + 0.6x = 2.7

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 0.6x = 2.7 + -2

Combine like terms: 2 + -2 = 0
0 + 0.6x = 2.7 + -2
0.6x = 2.7 + -2

Combine like terms: 2.7 + -2 = 0.7
0.6x = 0.7

Divide each side by '0.6'.
x = 1.166666667

Simplifying
x = 1.166666667

See similar equations:

| -10-7w-10=7-4w | | 4-3cot=1 | | 40=8(x-8) | | X^2-12X-4.5=0 | | P=2x+3 | | -8y=-6-9y | | -3(5+2x)=-2x+13 | | 8-(4x-12)=8x-(3x-2) | | 2-5f=-7f+10 | | 4+2y=10-4y | | 3/5=6n | | -j=j-8 | | -5x(4x-8y^2+4)= | | 10-6n=-6-10n | | 3b-11=3+b | | 7x-14=7(x+4) | | 5+10d=9d | | 6x-(10-2x)=3x+5 | | 9b+3=22 | | 18.9125-(1/4)= | | 9b+3=20 | | 9b+3=19 | | 2x^3-11x^2-10x+75=0 | | 9b+3=18 | | 9b+3=16 | | 4(t-3)+6t=5(2t+5)-12 | | 4x+3(2x-1)-4x=x | | a+4=a | | 4b+3=7 | | 4m^2-5=95 | | 2x+1x=126 | | (7)+11= |

Equations solver categories